Autism and ADHD in Tuberous Sclerosis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
In a population-based psychiatric study of 28 patients with tuberous sclerosis (TS) at the University of Goteborg, Sweden, 24 had autistic symptoms and 17 met all DSM-III-R criteria for autistic disorder (AD).